(untitled) (Research, Society and Development, 2023)
Drug interactions are health risk factors, and can be drug/drug interactions, food/drug and drug/alcohol interactions. These interactions can act on the effect of substances, inducing toxic effects or inhibiting the therapeutic effect of the drug. Alcohol and benzodiazepines have direct action on the central nervous system (CNS), both cross the blood-brain barrier (BHE) and reach GABA (Inhibitory Neurotransmitter), causing effects such as sedation and CNS depression. The bibliographic survey was carried out in the databases: SciELO, PubMED, LILACS and Google Scholar. In the periods from 2013 to 2022. Using the descriptors: Drug Interactions, Alcohol, Benzodiazepines, Clonazepam, Alcohol Metabolism and Clonazepam Metabolism, both combined with Boolean AND operator, found in Portuguese and English. However, of the total number of journals found, 4,846 did not meet the eligibility criteria, leaving only 13 titles for a more careful analysis of the selected topics. This study demonstrated that the inappropriate use of benzodiazepines, in particular Clonazepam, has adverse effects, especially if associated with other drugs such as alcohol. The objective of this work is to point out knowledge aimed at the inappropriate use of Clonazepam in conjunction with the consumption of alcohol. Taking into account the need for the guidance of the health professional, in order to avoid possible errors in drug treatment, which may result in greater damage to the health of the patient.